9*x^2-4*y^2+5*x+10=0 8*x^2-3*y^2+5*y+10=0

1 уравнение:
2 уравнение:
3 уравнение:
4 уравнение:
5 уравнение:
6 уравнение:
7 уравнение:
8 уравнение:
9 уравнение:
10 уравнение:
11 уравнение:
12 уравнение:
13 уравнение:
14 уравнение:
15 уравнение:
16 уравнение:
17 уравнение:
18 уравнение:
19 уравнение:
20 уравнение:
21 уравнение:
22 уравнение:
23 уравнение:
24 уравнение:
25 уравнение:
26 уравнение:
27 уравнение:
28 уравнение:
29 уравнение:
30 уравнение:
31 уравнение:
32 уравнение:
33 уравнение:
34 уравнение:
35 уравнение:
36 уравнение:
37 уравнение:
38 уравнение:
39 уравнение:
40 уравнение:
41 уравнение:
42 уравнение:
43 уравнение:
44 уравнение:
45 уравнение:
46 уравнение:
47 уравнение:
48 уравнение:
49 уравнение:
50 уравнение:
51 уравнение:
52 уравнение:

Решение

Вы ввели
[LaTeX]
   2      2               
9*x  - 4*y  + 5*x + 10 = 0
$$5 x + 9 x^{2} - 4 y^{2} + 10 = 0$$
   2      2               
8*x  - 3*y  + 5*y + 10 = 0
$$5 y + 8 x^{2} - 3 y^{2} + 10 = 0$$
Быстрый ответ
[LaTeX]
$$x_{1} = -2$$
=
$$-2$$
=
-2

$$y_{1} = -3$$
=
$$-3$$
=
-3
$$x_{2} = 9$$
=
$$9$$
=
9

$$y_{2} = -14$$
=
$$-14$$
=
-14
$$x_{3} = - \frac{5}{16} - \frac{9 i}{16} \sqrt{7} + \frac{1}{8} \left(- \frac{1}{2} - \frac{\sqrt{7} i}{2}\right)^{2}$$
=
$$- \frac{1}{2} - \frac{\sqrt{7} i}{2}$$
=
-0.5 - 1.3228756555323*i

$$y_{3} = - \frac{1}{2} - \frac{\sqrt{7} i}{2}$$
=
$$- \frac{1}{2} - \frac{\sqrt{7} i}{2}$$
=
-0.5 - 1.3228756555323*i
$$x_{4} = - \frac{5}{16} + \frac{1}{8} \left(- \frac{1}{2} + \frac{\sqrt{7} i}{2}\right)^{2} + \frac{9 i}{16} \sqrt{7}$$
=
$$- \frac{1}{2} + \frac{\sqrt{7} i}{2}$$
=
-0.5 + 1.3228756555323*i

$$y_{4} = - \frac{1}{2} + \frac{\sqrt{7} i}{2}$$
=
$$- \frac{1}{2} + \frac{\sqrt{7} i}{2}$$
=
-0.5 + 1.3228756555323*i
Численный ответ
[LaTeX]
x1 = -2.00000000000000
y1 = -3.00000000000000